Nonsingular spiked harmonic oscillator - Aguilera-Navarro, V. C. [UNESP]; Guardiola, R. (AIP Publishing, 1991)
A perturbative study of a class of nonsingular spiked harmonic oscillators defined by the Hamiltonian H= -d2/dr2 + r2 + λ/rα in the domain [0,∞] is carried out, in the two extremes of a weak coupling and a strong coupling regimes. A path has been found to connect both expansions for α near 2. © 1991 American Institute of Physics.